2003
DOI: 10.3168/jds.s0022-0302(03)73766-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Postnatal Mortality in Danish Holstein Calves

Abstract: The objective of this study was to estimate genetic parameters of postnatal mortality (PM) in dairy cattle. Data originated from 841,921 Danish Holstein calves. Four binary traits of mortality were considered: D1-14, D15-60, D61-180, and D1-180 with numbers indicating the period of risk in days after birth. The unadjusted frequency of D1-14, D15-60, D61-180, and D1-180 were 0.027, 0.018, 0.020, and 0.066, respectively. A linear sire-model was fitted to the data, and average information-REML was used to estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
77
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 26 publications
19
77
1
1
Order By: Relevance
“…from USA, Denmark and Holland show stillbirth rates of 10-13% in Holstein heifers comparable with those reported in Sweden (e.g. [3][4][5]). …”
Section: Introductionsupporting
confidence: 66%
“…from USA, Denmark and Holland show stillbirth rates of 10-13% in Holstein heifers comparable with those reported in Sweden (e.g. [3][4][5]). …”
Section: Introductionsupporting
confidence: 66%
“…Gulliksen et al (2009) reported a mortality rate of 3.7% in the first year of life in Norwegian dairy herds, while Svensson et al (2006) observed 3.1% of calves dying up to an age of 90 days in southwestern Swedish farms. In Denmark, 6.6% of Holstein calves (Hansen et al, 2003) and a rather alarming proportion of 12.5% of Jersey calves (Norberg, 2008) died up to an age of 180 days. Dystocia, respiratory diseases or pneumonia and diarrhoea are frequently mentioned as the most important factors influencing mortality in calves and heifers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study therefore is to explore the genetics of calf and heifer mortality in Austrian Fleckvieh (dual purpose Simmental) by (1) defining relevant periods for juvenile survival, as evidence from earlier studies (Hansen et al, 2003) suggests that survival of calves and heifers is different at different stages of their life and may therefore be controlled by different genes; (2) comparing different methods (linear and threshold models, sire and animal model) for estimating variance components and genetic parameters; and (3) implementing a genetic evaluation of the current Austrian Fleckvieh population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preweaning mortality is an important economic component of farming systems since it reduces the number of animals available for sale (Østerås et al, 2007), compromises animal well-being (Hansen et al, 2003), and reduces the number of animals available for selection as well as genetic progress (Fuerst-Waltl & Fuerst, 2010;Meyer et al, 2001). …”
Section: Introductionmentioning
confidence: 99%